Adrenal crises in older patients. Issue 7 (July 2020) - Rushworth, Ruth L; Torpy, David J; Falhammar, Henrik
Summary: Adrenal crises are severe manifestations of adrenal insufficiency that result in hospital admission and incur a risk of cardiovascular events, acute renal injury, and death. Evidence from population-based studies indicate that adults older than 60 years have the highest adrenal insufficiency incidence, contribute to the highest number of adrenal crises, and have the highest age-specific incidence of adrenal crisis, which doubles between the age groups of 60–69 years and 80 years or older. Older patients might be more susceptible to adrenal crises because of a higher prevalence of comorbidities and a consequently higher risk of acute illness. This susceptibility might be compounded by shortfalls in the implementation of prevention strategies for adrenal crisis, because of individual and social factors that increase with age. Although little research has focused on adrenal crisis prevention in older patients, it seems logical that a timely diagnosis of adrenal insufficiency and the use of consensus driven adrenal crisis prevention and attenuation strategies might reduce adrenal crises in patients older than 60 years old.